THE EFFECT OF SALES VOLATILITY, CASH FLOW VOLATILITY, AND OPERATING CYCLE ON PROFIT PERSISTENCE IN MANUFACTURING COMPANIES LISTED ON THE IDX IN 2022–2024 - Ferby Claudia; Harti Budi Yanti (RADJA PUBLIKA, 2025)
Profit persistence is a concern for investors and stakeholders in making investment decisions. To attract investors and creditors, companies tend to maintain stable profits each period. However, profit inconsistencies often occur, especially in manufacturing companies due to economic fluctuations, the impact of the pandemic, global inflation and geopolitical tensions. Therefore, investors need to be alert because profits that appear stable could be the result of income smoothing practices. The study was conducted with the aim of seeing the influence of sales volatility, cash flow volatility, and operating cycles on earnings persistence. The approach applied was quantitative by taking samples using non-probability sampling and applying the purposive sampling method, resulting in 14 manufacturing companies in the food and beverage sector listed on the IDX in 2022-2024. The analysis was carried out using multiple linear regression analysis with Eviews 12 software. The study findings prove that sales volatility has no influence on earnings persistence, while cash flow volatility shows a positive and significant effect on earnings persistence. This is different from the operating cycle which shows a negative and significant impact on earnings persistence for manufacturing companies listed on the IDX in 2022-2024. The importance of cash flow management and operating cycle efficiency in maintaining the stability of manufacturing companies' profits, so that they focus more on cash flow management and shortening the operating cycle to support earnings stability.